On some modification of the sum-quota sampling scheme - Gamrot, Wojciech (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2011)
A simple extension of the well-known sequential sum-quota sampling scheme is proposed. The modification facilitates the simultaneous examination of several sampling units between checks of the cost limit. This may speed up the data gathering process while some degree of control over the variable sample cost is still retained. It is proposed to estimate the population total of the studied characteristic under such a sampling scheme using empirical estimates of inclusion probabilities evaluated in a simulation study. It appears that at least in some situations the empirical Horvitz-Thompson estimator is approximately unbiased.
Mathematical Economics, 2011, Nr 7 (14), s. 83-92
Keywords: fixed-cost sampling; sum-quota sampling; empirical inclusion probabilities